Evidence for a Big Brother Effect in Survey-Based Fear of Crime Research - Ashbourne, Jessica (International Journal of Criminology and Sociology, 2014)
The objective of this study was to determine whether sibling sex and birth order have any influence on individuals' reported fear of crime levels. Based on literature relating to gender, socialization, vicarious fear for spouses and children, and sibling influence, three hypotheses were formed. It was expected that a) having siblings would be protective against fear, b) male fear of crime would increase with the number of younger sisters and c) female fear of crime would decrease with the number of older brothers. A total of 83 McMaster University undergraduate students completed a survey that included demographic questions and a fear of crime index. Results indicated the existence of a "big brother effect", whereby females with older brothers exhibited less fear of crime than other females. There was no statistically significant difference in fear of crime among those with and without siblings and no sex-specific sibling effects on fear of crime in males. Explanations of this result focused on female vulnerability, socialization and the particular influence of older brothers on their sisters' behaviour and characteristics. This study highlights the influence of siblings on fear of crime and provides impetus for future research